Conceptual Analysis of the Internalization of Moral Values in Islamic Religious Education through a Humanistic Approach - Safitri, Fatma Muji; Hilmi Ajjahidi, Muhammad (-, 2025)
The development of an increasingly dynamic era requires the world of education, including Islamic Religious Education, to continue to adapt to a change in learning paradigm that is more contextual, relevant, and humanitarian-oriented. Education is no longer only understood as a process of knowledge transfer, but as a space for the development of the potential of the student as a whole, both intellectually, emotionally and spiritually. Qualitative research using a library research approach, data analysis is carried out using the content analysis method, which aims to decipher, interpret, and provide a deep understanding of the content of the text that has been collected. The application of humanistic theory in the learning of Islamic Religious Education can strengthen the affective and spiritual dimensions of students, so that they not only understand religious teachings cognitively, but also internalize their values in real life. Thus, the learning of Islamic Religious Education based on a humanistic approach is expected to be able to give birth to a generation that has faith, morals, and is able to face the challenges of the times wisely. Humanistic learning theory emphasizes that the learning process must be human-centered both as a subject and an object of education by making human values the main foundation. An education system that is oriented to this approach emphasizes the importance of developing human dignity, sanity in thinking, and the ability to make choices based on beliefs and values that are believed. Education based on humanistic values is able to produce a generation of Muslims with noble character, integration can also hold responsibility in people's lives.